Case Report: Malignant perivascular epithelioid cell tumor with aggressive mediastinal invasion and pulmonary metastasis - Leach, Daniel F.; Margam S, Srivikram; Foster, Marissa; Adkison, Jarrod B. (Frontiers in Oncology, 2025)
Perivascular epithelioid cell tumors (PEComas) are rare, typically benign soft tissue tumors that can develop at various anatomic sites. Malignant PEComas are rarer entities but may present aggressively with metastasis to the lungs or local recurrence years after initial presentation. In unresectable or metastatic cases, treatment options are limited due to the resistance of PEComas to chemotherapy and radiotherapy. The present case describes a 59-year-old man with a highly aggressive malignant PEComa, which ultimately invaded the mediastinum and replaced the right middle and lower lobes of the lung despite systemic therapy with oral sirolimus and definitive radiotherapy. As only three prior cases have described malignant PEComas invading the mediastinum, we highlight the clinical course of such an aggressive cancer and review current treatment paradigms.